Execution cache-based microarchitecture for power-efficient superscalar processors. - Talpes, E. (IEEE Transactions on VLSI systems)
This paper investigates a possible solution to the problem of power consumption in superscalar, out-of-order processors by proposing a new microarchitecture, specifically designed to reduce increasing power requirements of high-end processors. More precisely, we show that by modifying the well-established superscalar processor architecture, significant savings can be achieved in terms of power consumption. Our approach aims at limiting the growing amount of power used in a typical processor for dynamic optimizations (including out-of-order scheduling and register renaming). Our proposed approach achieves significant power savings by reusing as much as possible from the work done by the front-end of a typical superscalar, out-of-order pipeline, via the use of a special cache nested deeply into the processor structure. By reusing instructions that are already decoded, reordered, and have their registers already renamed, the front end of the pipeline can be turned off for large periods of time with significant savings in the overall power consumption. Experimental results show up to 35% (30% on average) savings in average energy per committed instruction, and 35% (20% on average) savings in energy-delay product, with about 9% average performance loss, over a large spectrum of SPEC95 and SPEC2000 benchmarks.